Removing Bodies from the Grave from the Perspective of National Criminal Law and Islamic Law - Al Hilal, Prara; Rahmi, Atikah (Veteran Law Review, 2024)
Corpse removal is the process of moving the body of a person from one place to another. Sometimes, this is done at the request of the family, for cultural or religious reasons, or even for other reasons such as demolition of the burial site or redevelopment of the burial area. The purpose of this research is to find out the rule of law to answer the issue of grave transfer. This type of research is normative juridical research obtained from secondary data related to the object of research including related laws and court decisions. In this research, data analysis is carried out qualitatively, namely the selection of theories, principles, norms, doctrines and articles contained in the Law that are relevant to this research. Based on the results of the research, the criminal act of corpse removal has criminal law rules, namely in Article 180 of Law No. 1 of 1946 concerning the Criminal Code and in Article 271 of Law No. 1 of 2023 concerning the Criminal Code. The removal of corpses from the grave is also not justified by several Islamic scholars so that this is in line with criminal law. In the case that occurred in Donggala district based on the Donggala District Court Decision No. reg 11/Pid.B/2014/PN.Dgl the Panel of Judges sentenced the defendants to imprisonment for four months each